Yes, I'm a lesbian and I'm a muslim too - Nasser, Nazreen (2016)
This qualitative study aims to understand the ways in which Muslim lesbians negotiate their seemingly conflicting identities while constrained within the social structural setting of the home in Singapore. Ten in-depth, semi-structured, life story interviews were conducted with female respondents between the ages of 20 and 29 who identified as both lesbian and Muslim. These respondents were old enough to have established their self but young enough to still be living with their parents in the same household. As the home is a place that socialises the family into religion and family values, trying to negotiate their seemingly conflicting identities was challenging within the social structural setting of the Muslim family household. However, the individual’s subjective meaning making also greatly determines the ways in which she negotiates her identities.